2018
DOI: 10.1016/j.wasman.2018.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and mechanical properties of recycled polyethylene films contaminated by biopolymer

Abstract: Nowadays, with the increasing amount of biopolymers used, it can be expected that biodegradable polymers (e.g. PLA, PBAT) may appear in the petrol-based polymer waste stream. However, their impact on the recycling processes is not known yet; moreover, the properties of the products made from contaminated polymer blends are not easily predictable. Therefore, our goal was to investigate the rheological and mechanical properties of synthetic and biopolymer compounds. We made different compounds from regranulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus, "islands" of the biopolymer will cause an indication of fracture during mechanical testing (see further the discussion about the SEM micrographs). Gere and Czigany studied the addition of PLA to a mixed film waste consisting of HDPE and low density polyethylene (LDPE) [4]. When 2% of PLA was added, no significant changes in the tensile properties were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, "islands" of the biopolymer will cause an indication of fracture during mechanical testing (see further the discussion about the SEM micrographs). Gere and Czigany studied the addition of PLA to a mixed film waste consisting of HDPE and low density polyethylene (LDPE) [4]. When 2% of PLA was added, no significant changes in the tensile properties were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of small amounts of biopolymers contaminating conventional polymers is not well studied. Gere and Czigany studied the influence of PLA contaminating recycled polyethylene films [4]. It was concluded that 2% contamination of PLA gave tolerable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies [ 136–139 ] have been conducted on the mechanical recycling of the blend of conventional and biopolymers. Gere and Gzigany [ 136 ] investigated the mechanical and rheological properties of recycled PE films contaminated with PLA at various concentrations. They used a mixture of HDPE (50%) and LDPE (50%), whereas virgin PLA was used to minimize the influencing factors.…”
Section: Recyclingmentioning
confidence: 99%
“…If these materials are used for other applications (e.g., a computer mouse housing), the material will enter the conventional waste streams and will not be separated for further recycling steps due to the low volume in waste streams [23,24]. The residues will either be transferred to landfill or to incineration with energy recovery depending on the current end-of-life infrastructure in the respective country.…”
Section: Introductionmentioning
confidence: 99%